17β-Estradiol promotes the synthesis and the secretion of annexin I in the CCRF-CEM human cell line - Margarida Castro-Caldas; Carlos B. Duarte; Arsélio P. Carvalho; M. Celeste Lopes (Mediators of Inflammation)
Aims: Annexin I (ANXA1), a 37 kDa member of the annexin family of Ca2+-binding and phospholipidbinding proteins, is particularly abundant in various populations of peripheral blood leukocytes. Since this protein modulates the anti-inflammatory actions of the steroid hormones, the purpose of this study was to investigate the effects of the female sex steroid hormone, 17β-estradiol (E2β), on the synthesis and secretion of ANXA1 in the human CCRF-CEM acute lymphoblastic leukemia cell line.